AN ANALYSIS OF NON-ENGLISH STUDENTS’ UNDERSTANDING IN USING PRONOUNS: CORRECT AND ERROR PRONOUNS - Exnasia Retno Palupi Handayani; Cenderato Cenderato (STKIP Persada Khatulistiwa Sintang, 2023)
This study was to investigate the non – English students’ error in using pronouns at STAKat Negeri Pontianak. The participant of this research were 40 students of seconds semester in academic year 2022. This research used descriptive research to gather the information and analyzed the result of the test. The result of the data gathered from the test that was given to the students through Google Form. Based on the analysis, the students wrote 53,98% correct answer and 46.02% of the students still made errors in using pronouns. There were 4.4% errors were found in the used of subjective pronouns, 13.90% errors were found in the used of objective pronouns, 12.81% errors were found in the used of possessive pronouns, and 16.56% errors were found in the used of reflexive pronouns. The lowest errors were found in the used of subjective pronouns, and the highest error was found in the used of reflexive pronouns.Keywords: Non – English Students, Errors, Pronouns, clearly, professionally